Nebulized Amikacin and Fosfomycin for Severe Pseudomonas aeruginosa Pneumonia: An Experimental Study*. Issue 6 (June 2019) - Li Bassi, Gianluigi; Motos, Ana; Fernandez-Barat, Laia; Aguilera Xiol, Eli; Chiurazzi, Chiara; Senussi, Tarek; Saco, Maria A.; Fuster, Carla; Carbonara, Marco; Bobi, Joaquim; Amaro, Rosanel; De Rosa, Francesca; et al.
Abstract : Objectives: Latest trials failed to confirm merits of nebulized amikacin for critically ill patients with nosocomial pneumonia. We studied various nebulized and IV antibiotic regimens in a porcine model of severe Pseudomonas aeruginosa pneumonia, resistant to amikacin, fosfomycin, and susceptible to meropenem. Design: Prospective randomized animal study. Setting: Animal Research, University of Barcelona, Spain. Subjects: Thirty female pigs. Interventions: The animals were randomized to receive nebulized saline solution (CONTROL); nebulized amikacin every 6 hours; nebulized fosfomycin every 6 hours; IV meropenem alone every 8 hours; nebulized amikacin and fosfomycin every 6 hours; amikacin and fosfomycin every 6 hours, with IV meropenem every 8 hours. Nebulization was performed through a vibrating mesh nebulizer. The primary outcome was lung tissue bacterial concentration. Secondary outcomes were tracheal secretions P. aeruginosa concentration, clinical variables, lung histology, and development of meropenem resistance. Measurements and Main Results: We included five animals into each group. Lung P. aeruginosa burden varied among groups ( p < 0.001). In particular, IV meropenem and amikacin and fosfomycin + IV meropenem groups presented lower P. aeruginosa concentrations versus amikacin and fosfomycin, amikacin, CONTROL, and fosfomycin groups ( p < 0.05), without significant difference between these two groups undergoing IV meropenem treatment. The sole use of nebulized antibiotics resulted in dense P. aeruginosa accumulation at the edges of the interlobular septa. Amikacin, amikacin and fosfomycin, and amikacin and fosfomycin + IV meropenem effectively reduced P. aeruginosa in tracheal secretions ( p < 0.001). Pathognomonic clinical variables of respiratory infection did not differ among groups. Resistance to meropenem increased in IV meropenem group versus amikacin and fosfomycin + meropenem ( p = 0.004). Conclusions: Our findings corroborate that amikacin and fosfomycin alone efficiently reduced P. aeruginosa in tracheal secretions, with negligible effects in pulmonary tissue. Combination of amikacin and fosfomycin with IV meropenem does not increase antipseudomonal pulmonary tissue activity, but it does reduce development of meropenem-resistant P. aeruginosa, in comparison with the sole use of IV meropenem. Our findings imply potential merits for preemptive use of nebulized antibiotics in order to reduce resistance to IV meropenem. Abstract : Supplemental Digital Content is available in the text.